Exercise and Sports Activities in Patients with Heart Failure - Sidhi Laksono; Hillary Kusharsasmita (WMJ (Warmadewa Medical Journal), 2022)
Exercise training is an essential additional non-pharmacological method to treat heart failure patients that has been shown to have significant impacts on mortality, morbidity, exercise capacity and quality of life. Various type of training are developed to resolve the needs of heart failure patients, including those who want to participate in sport activities. It is critical and challenging to prescribe personalized exercise training program perfectly, therefore, this review provides brief overview of the advantages and recommendations to prescribe individualized type of exercise training including aerobic, resistance, respiratory, aquatic and competitive sport activities for patients with heart failure. A comprehensive electronic search was conducted using PubMed, Google Scholar, and ScienceDirect. The search was limited to English-language publications from 2004 to 2021. Hand searching of relevant journals and reference lists was also performed. Exercise training should be component of a comprehensive heart failure care approach. Each patient with heart failure may have a different endurance to tolerate the same relative training. Individualized exercise training combined with a preliminary examination improves disability while also decreasing morbidity and mortality Keywords: heart failure, nonpharmacological management, sport exercise